Design of Automatic Hand Sanitizer During the Covid 19 Pandemic - Rizky Amalia (Jurnal Pengabdian Nusantara, 2023)
At the beginning of 2020, the world was shocked by an incident of severe infection with unknown causes, which started with a report from China to the World Health Organization (WHO). Coronavirus is an RNA virus with a particle size of 120-160 nm. The effort to prevent the spread of the coronavirus is by maintaining cleanliness and health, by implementing health protocols (wearing a mask, washing hands, and keeping a distance). An innovation to break the chain of transmission of the coronavirus is to create an automatic hand sanitizer, a technology designed with the main components Arduino UNO, ultrasonic sensors, and servo motors to reduce interaction between humans in using hand sanitizers without touching a hand sanitizer pump. The purpose of designing an automatic hand sanitizer during the Covet 19 pandemic is to reduce the spread of the coronavirus and make hand sanitizers automatic and practical. The methods used include problem analysis, tool design, and planning, tool making, testing, and evaluation. This automatic hand sanitizer is for the community to minimize transmission by not touching the hand sanitizer container in public places.